ETNOMATEMATIKA DALAM TRANSAKSI JUAL BELI YANG DILAKUKAN PEDAGANG DI PASAR TRADISIONAL KABUPATEN KAIMANA - Fradi, La Ode; Laurens, Theresia; Mataheru, Wilmintjie (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2019)
This study aims to describe ethnomatematics of buying and selling transactions conducted by traders in the traditional market of Kaimana district. It is descriptive researches method with a qualitative approach that emphasizes process analysis. The research subject was one person. The research instrument was in the form of guidelines for observation, interviews, and field notes, which were used to find out how the subjects performed mental calculations. The techniques of analysis data are data reduction, data presentation, and conclusion. Based on the results of the study, it can be concluded that there ethnomatematics activity are show by counting activities in buying and selling transactions. For example, calculate the amount of goods purchased by the buyer, determine the amount of change from the buyer, and calculate the profit of the selling price of each item purchased